2017
DOI: 10.1002/aic.15796
|View full text |Cite
|
Sign up to set email alerts
|

MnOx promotional effects on olefins synthesis directly from syngas over bimetallic Fe‐MnOx/SiO2 catalysts

Abstract: The direct synthesis of lower olefins via the Fischer‐Tropsch reaction (FTO) has been performed over a series of Fe‐MnOx/SiO2 catalysts. The addition of MnOx could improve the dispersion of iron species, and promote the reduction of iron oxide during the activation and subsequent carburization. Moreover, the results of characterization demonstrated that MnOx could enhance the surface basicity of the catalysts due to electronic effects and promote the formation of iron carbides. For the first time, the intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…However, for these Co‐Mn/TiO 2 FTS catalysts, it was already found that the role is complex as MnO x was considered to be both a structural and electronic promotor, resulting in higher metal dispersions and lower hydrogenation activity. These findings are in line with a recent paper of Han and co‐workers who found that the addition of MnO x to a Fe/SiO 2 FTS catalyst increased the reaction rate (by for example, enhancing the dissociation adsorption of CO) and the olefin selectivity . Furthermore, these authors observed that MnO x improved the dispersion of supported FeO x , facilitating its reduction and enhanching the carburization of FeO x .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, for these Co‐Mn/TiO 2 FTS catalysts, it was already found that the role is complex as MnO x was considered to be both a structural and electronic promotor, resulting in higher metal dispersions and lower hydrogenation activity. These findings are in line with a recent paper of Han and co‐workers who found that the addition of MnO x to a Fe/SiO 2 FTS catalyst increased the reaction rate (by for example, enhancing the dissociation adsorption of CO) and the olefin selectivity . Furthermore, these authors observed that MnO x improved the dispersion of supported FeO x , facilitating its reduction and enhanching the carburization of FeO x .…”
Section: Resultssupporting
confidence: 91%
“…[55,56,64,65] However, for these Co-Mn/TiO 2 FTS catalysts, it was already found that the role is complex as MnO x was considered to be both a structurala nd electronic promotor,r esulting in higher metal dispersions and lower hydrogenation activity.T hese findings are in line with ar ecent paper of Han and co-workersw ho found that the addition of MnO x to aF e/SiO 2 FTS catalyst increasedt he reactionrate (by for example, enhancing the dissociation adsorption of CO) and the olefin selectivity. [66] Furthermore, these authors observed that MnO x improved the dispersion of supported FeO x ,f acilitating its reduction and enhanching the carburizationo fF eO x .I nterestingly,X iaohaoa nd coworkers have recently investigated the addition of MnO x to a Co/SiO 2 FTS catalyst. [67] These authors found that MnO x affects the formation of Co 2 C, ap hase which has been recently shown to have ah igh selectivity towards lower olefins.…”
Section: Resultsmentioning
confidence: 99%
“…Even a small amount of MnO x can improve the dispersion of FeO x and the carburization of Fe [88,101]. Kinetic studies further demonstrated the effect of MnO x on promoting CO dissociation and monomer formation, reducing the effective sites of H 2 dissociation, olefin reabsorption and secondary hydrogenation [102], which promoted the generation of low-carbon olefins. Unlike CO hydrogenation, Kuei et al [103] concluded that manganese showed little promotion effect on the selectivity of olefinic hydrocarbons in CO 2 hydrogenation.…”
Section: Bimetallic Catalystsmentioning
confidence: 94%
“…Our previous work has demonstrated that H 2 could adsorb on the surface competitively with CO and other species. 63 Therefore, the adsorption of H 2 on the surface is expected to be weakened, given that CO adsorption is promoted on χ-Fe 5 C 2 /MgO. Li et al 64 found that H 2 adsorption on surface Fe sites could be suppressed with the addition of MgO and became stronger with the increase of the MgO amount.…”
Section: Mgo As An Electronic Promotermentioning
confidence: 99%